Prospective assessment of perioperative course in 2648 patients after surgical treatment of benign prostatic obstruction - Bach, Thorsten (World journal of urology, 2017)
Purpose: TUR-prostate (TUR-P) is considered the reference method for surgical treatment of benign prostatic obstruction (BPO); Greenlight laser photoselective vaporization (PVP) and thulium laser vapoenucleation (ThuVEP) have also been established as treatments of BPO. Objective of this prospective observation was to compare a large numbers of patients treated in everyday routine. Methods: This prospective multicentre data collection assesses morbidity and perioperative course of consecutive men treated with BPO-related transurethral surgery between 2011 and 2014 in a German metropolis area with TUR-P, PVP or ThuVEP. Results: Two thousand six hundred and forty-eight patients have been treated in the time period. All treatment options achieved immediate improvement of voiding parameters. Multivariate analyses proved shorter hospital stay after laser treatments as compared to resection (p < 0.001). In terms of hospital stay, the advantage of ThuVEP compared to TUR-P increased with prostate volume (p < 0.001). Patients with ongoing anticoagulation or bridging had prolonged hospital stay (p < 0.001). Overall adverse events were least frequent in PVP (p 0.016), as were Clavien 3b events (p < 0.001). Conclusions: Surgical treatment of BPO is effective and safe independent of the surgical procedure. Volume reduction is most effective in ThuVEP; PVP has the lowest rate of severe complications. Laser treatment is associated with shorter hospital stay. Surgery under ongoing anticoagulation prolonged the post-operative hospital stay.